Cooperative OFDM relaying for opportunistic spectrum sharing : protocol design and resource allocation - Lu, Wei Dang. (2013)
In this paper, we propose an opportunistic spectrum sharing protocol that exploits the situation when the primary system is incapable of supporting its target transmission rate. Specifically, the secondary system tries to help the primary system to achieve its target rate via two-phase cooperative OFDM relaying, where the secondary system acts as an amplify-and-forward relay for the primary system by allocating a fraction of its subcarriers to forward the primary signal. At the same time, the secondary system uses the remaining subcarriers to transmit its own signal, and thus gaining opportunistic spectrum access. As a part of the protocol, if the primary system finds that outage will occur even when the secondary system serves as a pure relay, the primary system will cease transmission and the secondary system will be granted access to the primary spectrum. We study the joint optimization of the set of subcarriers used for cooperation, subcarrier pairing, and subcarrier power allocation such that the transmission rate of the secondary system is maximized, while helping the primary system, as a higher priority, to achieve its target rate. Simulation results demonstrate the performance of the proposed spectrum sharing protocol as well as the win-win solution for the primary and secondary systems.